India : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
The Indian economy has recovered strongly. The government's poverty alleviation programs have focused on generation of employment in rural areas. The overall deficit of the consolidated public sector has risen sharply in recent years, erasing most of the consolidation that was achieved during the first half of the 1990s. The paper discusses the monetary and financial market developments, reforms and performance, external sector, trade policy, and structural policy developments in India. The new government has taken a number of initiatives committed to structural reform.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet